Dissenting praise: religious dissent and the hymn in England and Wales - Wykes, David L.; Rivers, Isabel (Oxford University Press, 2011)
This is a comprehensive study of the dissenting hymn in England and Wales. The chapters cover a wide range of topics, including the style, language, and theology of hymns; their editing publication, and reception; their role in promoting evangelical Christianity; and their shaping of denominational identities